RIP2 Contributes to Expanded CD4+ T Cell IFN-g Production during Efferocytosis of Streptococcus pneumoniae–Infected Apoptotic Cells - Niño-Castaño, Victoria Eugenia [UNESP]; de Aquino Penteado, Letícia [UNESP]; Silva-Pereira, Ludmilla [UNESP]; Bazzano, Júlia Miranda Ribeiro [UNESP]; Orlando, Allan Botinhon [UNESP]; Salina, Ana Carolina Guerta [UNESP]; Dejani, Naiara Naiana; Bonato, Vânia L.D.; Serezani, C. Henrique; Medeiros, Alexandra Ivo [UNESP] (Oxford University Press (OUP), 2022)
Apoptotic cell clearance by professional and nonprofessional phagocytes in the process of efferocytosis is critical to preserve tissue homeostasis. Uptake of apoptotic cells by dendritic cells generates regulatory T cells and induces immunologic tolerance against self-antigens. In contrast, ingestion of infected apoptotic cells promotes activation of TLR4/MyD88-dependent bone marrow–derived dendritic cells (BMDCs) and triggers Th17 cell differentiation. In this study, we evaluated the impact of Streptococcus pneumoniae–infected apoptotic cell efferocytosis by BMDCs derived from C57BL/6 mice on differentiation and expansion of CD4+ T cell subsets, as well as the role of TLR2/4 and receptor-interacting protein 2 (RIP2) receptors in recognizing intracellular pathogens during efferocytosis. We demonstrated that BMDC-mediated efferocytosis of S. pneumoniae–infected apoptotic cells induced Th1 cell differentiation and expansion. Although TLR2/4 and RIP2 deficiency in BMDCs did not affect Th1 cell differentiation during efferocytosis, the absence of RIP2 decreased IFN-γ production by CD4 T cells during the expansion phase. These findings suggest that RIP2-mediated IL-1β production during efferocytosis of S. pneumoniae–infected apoptotic cells partially supports a Th1-mediated IFN-γ production microenvironment.